2018
DOI: 10.21278/brod69303
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Cracks Detection in Marine Structures' Welded Joints Based on Signals' Time Waveform Analysis

Abstract: The paper presents two methods of crack detection in ship hulls. The methods are dedicated for structural health monitoring (SHM) of responsible welded joints. The system will be based on vibrodiagnostic-signals will be measured by piezoelectric accelerometers and/or fibre optic sensors. In SHM systems of welded joints of thin-walled structures, a vibrodiagnostic method is the most promising. Its most important advantage is that it is both effective and relatively low costly. There are two general methods of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This opportunity is often used in the analysis of technical systems dynamics, especially electrical or electronic ones. It is used in mechanical systems testing very rarely (Muc, et. al., 2018).…”
Section: Time Window Methods In Time-frequency Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This opportunity is often used in the analysis of technical systems dynamics, especially electrical or electronic ones. It is used in mechanical systems testing very rarely (Muc, et. al., 2018).…”
Section: Time Window Methods In Time-frequency Analysismentioning
confidence: 99%
“…Conducted tests aimed at the optimal coverage of spectrums characteristic changes which determine the quality of welds and possible defects. The optimal width of the window was chosen as 10 ms for analyzed plates (Muc, et. al., 2018).…”
Section: Time Window Methods In Time-frequency Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Result of the experiment indicated that the mechanical behavior of the system could be imagined quite well with the proposed prototype. A. Muc et al [10] in 2018 presented dual techniques for detecting cracks in the ship hulls. Proposed method was fully defined for structural health monitoring (SHM) of responsible welded joints of materials.…”
Section: Tungsten Inert Gas Weldingmentioning
confidence: 99%
“…Benefits of the technique have motivated many researchers to develop various automatic crack detection methods utilizing image processing methods. [10] These methods show good results in case of quantitative analysis based on objectivity while the visual crack estimation is very tedious and also dependent on the specialist person knowledge and experience also. The overall setup of the crack estimation using camera consist of high resolution camera, image denoising and enhancement filters, crack detection algorithms and crack feature extraction detectors.…”
Section: Introduction a Developmentmentioning
confidence: 99%